1995
DOI: 10.1021/jm00001a009
|View full text |Cite
|
Sign up to set email alerts
|

Relative Binding Free Energies of Peptide Inhibitors of HIV-1 Protease: The Influence of the Active Site Protonation State

Abstract: Hydrogen bonding plays an important role in the stabilization of complexes between HIV-1 protease (HIV-1 PR) and its inhibitors. The adequate treatment of the protease active site protonation state is important for accurate molecular simulations of the protonation state is important for accurate molecular simulations of the protease-inhibitor complexes. We have applied the free energy simulation/thermodynamic cycle approach to evaluate the relative binding affinities of the S vs R isomers of the U85548E inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 8 publications
2
37
0
Order By: Relevance
“…Such methods can be quite successful in identifying lead compounds (Lam et al, 1994). More sophisticated and expensive calculations have applied the free energy perturbation method in order to evaluate changes in binding energy upon substitution of small molecular fragments (Reddy et al, 1994;Chen & Tropsha, 1995). The current state of the art in molecular simulations of HIV-I-PR inhibitor binding was reviewed by McCarrick and Kollman (1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such methods can be quite successful in identifying lead compounds (Lam et al, 1994). More sophisticated and expensive calculations have applied the free energy perturbation method in order to evaluate changes in binding energy upon substitution of small molecular fragments (Reddy et al, 1994;Chen & Tropsha, 1995). The current state of the art in molecular simulations of HIV-I-PR inhibitor binding was reviewed by McCarrick and Kollman (1994).…”
Section: Discussionmentioning
confidence: 99%
“…These interactions result in an almost complete burial of most HIV-I-PR inhibitors. Conclusions about the energetic contributions to the total binding strength of these inhibitors, based largely on applications of conventional modeling tools (Hutchins & Greer, 1991;Appelt, 1993;Guida, 1994;Chen & Tropsha, 1995;Holloway et al, 1995), find that hydrogen bonding patterns and hydrophobic interactions are frequent components of inhibitor binding (Appelt, 1993;Wlodawer & Erickson, 1993;Gustchina et al, 1994). The extent and importance of these interactions have, however, been difficult to characterize.…”
Section: Hiv-1 Protease Inhibitorsmentioning
confidence: 99%
“…A number of research groups, using a variety of techniques-including solution NMR, have concluded that one of the two aspartate residues located in the catalytic domain of HIV protease is protonated, while the other is negatively charged. [52][53][54] Similarly, the determination of pK a values for all carboxyl groups in ribonuclease HI indicated that for two aspartate residues in close proximity, one has an elevated pK a , while the other has a depressed pK a ; i.e., one of the residues is protonated. 55 Other studies have demonstrated that the desolvation of acidic residues can result in pK a shifts toward or past the environmental pH, occurring most often with acidic residues found in areas of proteins that insufficiently stabilized their negative charge, and/or were hydrophobic in nature.…”
mentioning
confidence: 99%
“…Additional successful applications of the FEP method for the calculation of HIV-1 PR inhibition, including non-peptide inhibitors, have been reported by McCarrick and Kollman [86], Rao and Murcko [87], Varney et al [88], Chen and Tropsha [89], and Wang et al [90] and has laid the path for more recent accomplishments in FEP guided design of HIV-1 reverse transcriptase inhibitors.…”
Section: Hiv-1 Prmentioning
confidence: 99%